Base Deficit as a Predictor of Mortality in Sepsis and Septic Shock - Bhusal, Laxman; Prasad, Pratap Narayan; Shakya, Yogendra Man; Acharya, Ramesh Prasad (Journal of Karnali Academy of Health Sciences, 2019)
Introduction: Sepsis is a common problem encountered in emergency room which needs to be intervened early. It is always difficult to have quick prognostic marker of sepsis in busy emergency. So this study was conducted to determine whether base deficit can be used as an indicator of mortality among septic patients in emergency room setup like ours. Methods: It was a hospital based descriptive cross sectional study done at Tribhuvan University Teaching Hospital, Kathmandu from March 2018 to December 2018. Acute physiology and chronic health Evaluation II score (APACHE II), Base deficit, Sequential Organ Failure Assessment (SOFA) score on first day of arrival in emergency room was calculated. The association of 28-day outcome with acute physiology and chronic Health Evaluation II score, Base deficit value and SOFA score were derived. Results: Out of 229 patients with septic shock 62 died (27%) and among 71 patients without septic shock, 12 died (16.9%).Overall mortality was 24.66 % (n= 74).The area under the ROC curve for Base deficit(0.864;95% C.I.=0.822-0.906), APACHE II (0.782; 95% C.I=0.718-0.848, SOFA (0.689;95% C.I=0.620-0.757) were greater than 0.7 except for SOFA which signifies these test to have fair efficacy to predict mortality. Conclusions: High base deficit value predicts mortality in patients with sepsis and septic shock. The base deficit could be used as an alternate marker to predict mortality in septic patient. We recommend for large multicenter study with randomization so that the findings can be applied to general population and of different geographical situations.